Current Status of Hydrothermal Treatment for Energy and Material Recovery Toward a Sustainable Post-consumer Material Cycle - Lokahita, Baskoro; Aziz, Muhammad; Takahashi, Fumitake (Makara Journal of Technology, 2020)
The demand for energy-efficient and environmentally friendly municipal solid waste (MSW) processing has increased in developing countries. The thermochemical process offers a fast and reliable solution to reutilize or reduce the volume of MSW. Hydrothermal treatment is a novel MSW treatment technology that is compatible with high-moisture-content feedstock. It involves the thermal degradation of MSW in pressurized water or steam, which promotes the disintegration of cellulosic and polymer materials. Recent advances have shown effective MSW conversion into homogenous solid hydrochar with higher energy density. Alkali and chlorine content, which causes issues in combustors, was successfully removed due to the washing effect of hydrothermal treatment. The possibility of activated carbon production also exists because the surface area is significantly increased after the treatment. This paper presents an overview of the latest development of hydrothermal treatment in the field of post-consumer waste and MSW treatment, with particular focus on the operating conditions and physicochemical characteristics of the hydrochar. Several experimental results from post-consumer waste feedstock were compiled and interpreted using principal component analysis to observe the effect of different operating conditions and feedstock during the hydrothermal process.